The role of adipose tissue in puberty and reproductive health - Ning, Xin; Huang, Qing; Guo, Doudou; Zhou, Yanfen; Li, Yating; Li, Xin (Frontiers in Endocrinology, 2025)
Adipose tissue is an endocrine organ that signals energy status to the hypothalamic–pituitary–gonadal axis to regulate reproductive function. Notably, in mammals, adipose tissue biology—adipose tissue expansion and body fat distribution—is closely linked to the onset of puberty. Some studies showed that early adipose tissue development continues into childhood or adulthood, indicating its potential impact on reproductive function. Factors such as maternal obesity, childhood body mass index gain, and adolescent obesity significantly contribute to early puberty onset and negative reproductive events including menstrual irregularity, polycystic ovary syndrome, and male infertility. However, the connection between adipose tissue development before adulthood (prenatal stage and childhood) and reproductive function has not yet been fully investigated and reviewed. In this study, we present a comprehensive review of hormonal and inherent dimorphisms on adipose tissue development; there is a novel discussion about the link between adipose tissue expansion tracking throughout early life stages and reproductive disorders. Our study aims to elucidate how adipocyte development during critical periods of life can affect future reproductive health from sexual maturation to fertility and points to the clinical significance of further unlocking the underlying mechanism and weight management. As such, early prevention and long-term management for weight control might be considered as effective measures to mitigate obesity-induced reproductive comorbidities.